Evolution of modern humans is a result of self-amplifying feedbacks beginning in the Miocene and continuing without interruption until now - Henneberg, Maciej; Eckhardt, Robert B. (Anthropological Review, 2022)
Humans are a part of the complex system of life. This consists of a multitude of feedbacks among all parts of living systems. In the case of human origins, many feedbacks became positive rather than homeostatic, thus producing self-amplifying effects in basic morphological and behavioural characteristics of emerging humans: erect bipedalism, social structure, tool-making, food procurement and environmental management, symbolic communication, sexuality, extended childhood, and mental capacities. These, plus many other human characteristics, changed gradually, though at varying rates, over the last 6 million years, producing directional variation in extant morphological and behavioural characteristics of what are considered modern humans. The change through time and geographic space of those characteristics is an ongoing dynamic process, thus it is futile to pose essentialist questions about the precise date and place of the modern human origins. Modernity is a process, not an endpoint.